Organizational Culture in Academic Institutions Hofstede’s Five Dimensions: Array - Ukshini, Kosovare; Ziberi, Besime (Journal of Danubian Studies and Research, 2020)
Organizational culture is a case that has a big attention in the world of globalization economy. Nowadays we can hear different kind of debates and also we can find a lot of research papers that are related with organizational culture. In most of research papers we can find different definitions of the organizational culture but in context the concept of culture means the same: “Culture is how organizations do things’.” — Robbie Katanga. Most simple cultures involve three basic human activities: what people think, what people do and what people make. Organizational culture has to be oriented in highly positive virtues, attitudes, and behavior of employees and management that are part of individuals who work together to achieve organizational goals in effective and efficient way. These individuals share their attitudes, values, beliefs between organization, with costumers and furniture and with the whole factors that directly or indirectly are related with the organization work. Organizational culture is a big matter for all types of organizations because it has very important effect on the company’s success and the whole wellbeing. In this research paper is showed a picture of the organizational culture in academic institutions regarding to Hoffstede’s five dimensions for culture.